A review of the Afrotropical genus Mycomyiella Matile, 1973 (Diptera, Mycetophilidae, Mycomyini), with the description of six new species - Gammelmo, Øivind (Zootaxa, 2004)
Systematics of the genus Mycomyiella are reviewed. A generic diagnosis, description and illustrations of the males are provided. Nine species are recognized, of which 6 are newly described: M. diseta new species (Tanzania), M. elegans new species (Tanzania), M. ghanaensis new species (Ghana), M. kaputuensis new species (Tanzania), M. tannerorum new species (Tanzania), and M. wangi new species (Tanzania). The phylogeny of Mycomyiella is outlined, placing it as the sister group of Mycomya Rondani, 1856. The monophyly of Mycomyiella is well supported, and two species groups can be recognized, one including M. camerounensis Matile, 1973, M. irwini V is nen, 1994, M. ghanaensis, M. securiculata Matile, 1973, M. diseta and M. kaputuensis, the other including M. elegans, M. tannerorum and M. wangi.